MENINGKATKAN KEMAMPUAN MENULIS MELALUI STRATEGI DIRECTED WRITING ACTIVITY - Hasbiyah Srianah Amir (Jurnal Panrita, 2022)
Improving writing ability through directed writing activity strategy of the tenth-year students. This research is to find out whether or not the Directed Writing Activity strategy able to improve the writing ability. The writer applied quasi-experimental method, with two group control and experimental class. The result of the data analysis on mean score of pre-tests was 60.23 and the mean score of post-tests was 83.97. After analyzing the data by using the test formula, the result of t-test value was 6.23 and t-table value was 1.671. It means that the t-test value was greater than t-table value (1.671). This indicated that h1 was accepted and h0 was rejected. It shows that directed writing activity strategy able to improve the students’ writing ability and there is significant difference of the students’ writing ability before and after giving treatment through directed writing activity strategy.